PENGARUH RISIKO KREDIT TERHADAP TINGKAT PROFITABILITAS PADA BANK UMUM GO PUBLIC PERIODE TAHUN 2014 - Melania, Lenny; Indrawati, Henny; ', Gusnardi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : The purpose of this study was to demonstrate empirically the effect of credit risk on the level of Profitability in Commercial Banks go public . The sampling technique used is the census , with a sample of some 42 commercial banks that go public period of 2014. The analysis technique used is a simple linear regression . The results of this study indicate that : Credit Risk negative effect on the level of commercial bank profitability that go public . The test results demonstrate the contribution of Credit Risk influence on the level of profitability was 13.2 % , while 86.6 % are influenced by other factors not included in this research model .Keywords : Credit Risk , Profitability